1998
DOI: 10.1046/j.1365-313x.1998.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

The GCN4 motif in a rice glutelin gene is essential for endosperm‐specific gene expression and is activated by Opaque‐2 in transgenic rice plants

Abstract: SummaryThe GCN4 motif is conserved in a number of seed storage protein genes, and promoter fragments containing this motif have been shown to be involved in controlling seed-specific expression of the genes studied. All genes encoding the rice seed storage protein glutelin contain the GCN4 motif at similar sites in their 5Ј flanking regions. Using a stable homologous transgenic system, we have analysed the promoter of the rice glutelin gene GluB-1 and demonstrated that the GCN4 motif functions as an essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
141
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 48 publications
3
141
1
1
Order By: Relevance
“…In vivo foootprinting of the promoter region of wheat low molecular weight glutenin (16) and maize ␥-zein genes (6) in developing endosperm revealed that the region covering the GCN4 motif and prolamin box are occupied by nuclear proteins from maturing seeds. In vitro DNase I footprinting with nuclear proteins from rice maturing seeds and GST-O2 fusion protein also showed that the sequence covering the GCN4 motif in the promoter of glutelin genes is specifically protected from DNase I digestion (8,17). These findings suggest that O2-like transcription factor may exist and participate in controlling the endosperm-specific expression of many storage protein genes in cereal seed through the GCN4 motif.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…In vivo foootprinting of the promoter region of wheat low molecular weight glutenin (16) and maize ␥-zein genes (6) in developing endosperm revealed that the region covering the GCN4 motif and prolamin box are occupied by nuclear proteins from maturing seeds. In vitro DNase I footprinting with nuclear proteins from rice maturing seeds and GST-O2 fusion protein also showed that the sequence covering the GCN4 motif in the promoter of glutelin genes is specifically protected from DNase I digestion (8,17). These findings suggest that O2-like transcription factor may exist and participate in controlling the endosperm-specific expression of many storage protein genes in cereal seed through the GCN4 motif.…”
mentioning
confidence: 78%
“…Multimers of the rice glutelin GCN4 motif can direct endosperm-specific expression in stable transgenic rice. In contrast, deletion or base substitution of the GCN4 motif in the rice glutelin promoter reduces promoter activity and alters gene expression pattern (8). The GCN4 motif is often linked together with the prolamin box (TGTAAAG), which are separated by a few nucleotides.…”
mentioning
confidence: 99%
See 3 more Smart Citations